2022
DOI: 10.1001/jamacardio.2022.2222
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Early Left Ventricular Ejection Fraction Improvement After Transcatheter Aortic Valve Replacement and 5-Year Clinical Outcomes

Abstract: In patients with severe aortic stenosis and left ventricular ejection fraction (LVEF) less than 50%, early LVEF improvement after transcatheter aortic valve replacement (TAVR) is associated with improved 1-year mortality; however, its association with long-term clinical outcomes is not known.OBJECTIVE To examine the association between early LVEF improvement after TAVR and 5-year outcomes. DESIGN, SETTING, AND PARTICIPANTSThis cohort study analyzed patients enrolled in the Placement of Aortic Transcatheter Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…Prior studies have also showed that in patients with LVEF < 40%, almost half of them experience an improvement in EF by at least 10% within 30 days after TAVR [ 9 , 10 ]. Recently, Dhaval Kolte et al published data on the 5-year all-cause death and cardiac death for a cohort of high- or intermediate-risk patients with severe AS and EF < 50% from the PARTNER trial, showing lower mortality in patients who experienced an improvement in LVEF after TAVR [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also showed that in patients with LVEF < 40%, almost half of them experience an improvement in EF by at least 10% within 30 days after TAVR [ 9 , 10 ]. Recently, Dhaval Kolte et al published data on the 5-year all-cause death and cardiac death for a cohort of high- or intermediate-risk patients with severe AS and EF < 50% from the PARTNER trial, showing lower mortality in patients who experienced an improvement in LVEF after TAVR [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…LVEF increase ≥5 or ≥10%) following TAVR has been reported in 22-48% of patients with LVSD at 30 days (Figure 1). 7,12,[18][19][20] In the PARTNER I trial, LVEF increased at 30 days and 6 months post-TAVR in patients with pre-existing LVEF <50%, with nearly 35% of patients undergoing transfemoral access and 22% of patients undergoing transapical access experiencing a ≥10% absolute increase in LVEF at 30 days. 12 Predictors of LVEF recovery have included female sex, absence of prior percutaneous coronary intervention (PCI), absence of peripheral vascular disease, lower baseline LVEF, and lower stroke volume index.…”
Section: Aortic Valve Gradient In Left Ventricular Systolic Dysfunctionmentioning
confidence: 99%
“…Left ventricular ejection fraction recovery (i.e. LVEF increase ≥5 or ≥10%) following TAVR has been reported in 22–48% of patients with LVSD at 30 days ( Figure ) 7,12,18–20 . In the PARTNER I trial, LVEF increased at 30 days and 6 months post‐TAVR in patients with pre‐existing LVEF <50%, with nearly 35% of patients undergoing transfemoral access and 22% of patients undergoing transapical access experiencing a ≥10% absolute increase in LVEF at 30 days 12 .…”
Section: Transcatheter Aortic Valve Replacement In Patients With Left...mentioning
confidence: 99%
“…Furthermore, it is well documented that each improvement of 5% points in LVEF at 30 days was linked to a 6% and 10% lower risk of all-cause and cardiac death at 5 years, respectively, indicating that early LVEF improvement after TAVR was associated with lower 5-year all-cause death and cardiac death. 4 Thus, the prognostic significance of LVEF improvement may be related to reduced mortality in patients after TAVR. These aspects need to be refined further in later clinical research.…”
Section: To the Editormentioning
confidence: 99%